2004
DOI: 10.1007/978-3-540-25967-1_12
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing in Agile Software Teams

Abstract: Abstract. Traditionally, software development teams follow Tayloristic approaches favoring division of labor and, hence, the use of role-based teams. Role-based teams require the transfer of knowledge from one stage of the development process to the next. As multiple stages are involved, the problem of miscommunication due to indirect and long communication path is amplified. Agile development teams address this problem by using cross-functional teams that encourages direct communication and reduces the likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 7 publications
1
49
0
11
Order By: Relevance
“…Agile teams share knowledge through several practices [10]: pair programming, release and sprint planning, customer collaboration, cross-functional teams, daily scrum meetings and project retrospectives. But, the authors [10] argue that, these practices are team-oriented and rely on face-to-face interaction between team members. These practices do not facilitate knowledge sharing in distributed agile teams but are effective for collocated and small teams.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Agile teams share knowledge through several practices [10]: pair programming, release and sprint planning, customer collaboration, cross-functional teams, daily scrum meetings and project retrospectives. But, the authors [10] argue that, these practices are team-oriented and rely on face-to-face interaction between team members. These practices do not facilitate knowledge sharing in distributed agile teams but are effective for collocated and small teams.…”
Section: Related Workmentioning
confidence: 99%
“…Not satisfied (0-3), Satisfied (4)(5)(6) and Highly satisfied (7)(8)(9)(10) Dispersed teams-α, β, δ; Distributed teams-γ, ε, ζ; Hybrid team-η Though teams face different types of challenges during knowledge sharing among distributed team members, we identified successful knowledge sharing in both locally and globally distributed agile teams from the seven cases studied. Based on the seven cases the above graph (see Figure 2) has been drawn.…”
Section: Challenges Faced By Practitioners During Knowledge Sharinmentioning
confidence: 99%
“…Chau and Maurer [14] describe that Agile teams share knowledge through several practices: release and sprint planning, pair-programming, on-site customers, cross-functional teams, daily Scrum meetings, and project retrospectives. They argue that these practices are team-oriented and rely on face-to-face interaction between team members.…”
Section: Related Workmentioning
confidence: 99%
“…Some of these tools offer message threads and project wiki for knowledge sharing. The use of wiki was also advised by Chau et al [11] and Auer et al [12]. However, in a case study based on suggestions from [7], Korkala et al found email to be the preferred medium for sharing knowledge in asynchronous communication [13].…”
Section: Related Workmentioning
confidence: 99%